Pyrolysis of Various Plastic Wastes for Liquid Fuel Production and Analysis of Liquid Hydrocarbon Fuels - Dr. Ruchir M Lashkari, Prof. Ashwin Parihar, Prof. Rituraj Raghuvanshi, Tanishq Gour, Tanishq Singh kushwah, Naveen kumar, Divyansh Sharma (Journal of Neonatal Surgery, 2025)
The consumption of plastics has been on a sharp rise in the 21st century pyrolysis is a efficient method in dealing with single use and waste plastic which doesn’t naturally breakdown, and ends up in landfills. Pyrolysis of polyethylene (PE), polypropylene (PP) & Ultra high molecular weight polyethylene (HM) plastic waste in the form of carry bags & packaging bags was carried out within a fabricated steel reactor in which no exchange of air takes place. Experiments were carried out individually for each type of plastic used as they possess different physical & chemical properties. For the reaction plastics of about 120-150 grams were used. A vacuum environment was created by using a seal in steel reactor. Reactor was kept in muffle furnace & temperature around 370˚C-550˚C was kept in the reactor. Reaction was carried out in the presence of Activated carbon as a catalyst. It was found that at temperature around 350˚C -370˚C liquid fuel started coming out from the reactor for polyethylene (PE), at temperature around 380˚C-390˚C for ultra-high molecular weight polyethylene (HM) & at 370 ˚C-410˚C for Polypropylene. Time required for completion of pyrolysis process was around 2.5-4.0 hrs. Analysis of oil samples of PE, PP and HM were done on Atomic Absorption Spectroscopy (AAS) for determination of heavy metals calorific value of oil sample was done by digital bomb calorimeter. The results showed that the oil samples contained nil amounts of lead & extremely low levels of sulphur contents.